Haptic Glove Using Tendon-Driven Soft Robotic Mechanism - Baik, Siyeon; Park, Shinsuk; Park, Jaeyoung (Frontiers in Bioengineering and Biotechnology, 2020)
Recent advancements in virtual reality and augmented reality call for light-weight and compliant haptic interfaces to maximize the task-performance interactivity with the virtual or extended environment. Noting this, we propose a haptic glove using a tendon-driven compliant robotic mechanism. Our proposed interface can provide haptic feedback to two fingers of a user, an index finger and a thumb. It can provide both cutaneous and kinesthetic feedback to the fingers by using the tendon-driven system. Each actuator is paired with a force sensor to exert the desired tension accurately. In order to optimize the perception of the kinesthetic feedback, we propose a perception-based kinesthetic feedback distribution strategy. We experimentally measured the force perception weight for peripheral interphalangeal (PIP) and metacarpophalangeal (MCP) joints. We observed no significant difference in the force perception between the two joints. Then, based on the obtained weights, our proposed force distribution method calculates the force for each joint. We also evaluated the effect of additional cutaneous feedback to the kinesthetic feedback, on the force perception at the fingertip. The experimental result has shown that additional cutaneous feedback has significantly increased the sensitivity of the human perception. Finally, we evaluated our proposed system and force distribution algorithm by conducting a human subject test. The experimental result indicates that the availability of the cutaneous feedback significantly improved the perceived realism and acuity of the contact force.